Thực trạng tiêm vắc xin phòng một số bệnh truyền nhiễm của sinh viên y khoa Trường Đại học Y Dược Thái Nguyên giai đoạn 2022 - 2025 - Quyên, Nguyễn Thị; Linh, Hoàng Diệu Hương; Hưng, Nguyễn Tiến; Hoàng, Trần Thế; Việt, Bùi Hồng; My, Nguyễn Trà (Tạp chí Nghiên cứu Y học, 2026)
Vaccination is a specific preventive measure that enables the body to develop artificial active immunity against infectious diseases. A cross-sectional study was conducted using direct surveys on 1,195 students at Thai Nguyen University of Medicine and Pharmacy to study the current status of vaccination against selected infectious diseases among medical students from 2022 to 2025. The results showed a very high vaccination coverage for the COVID-19 vaccine (97.4%), while other vaccines such as influenza, hepatitis B, and HPV had relatively low rates (below 30%). Notably, the coverage rates for vaccines against diseases such as cholera, typhoid, pneumococcal disease, hepatitis A, and meningococcal disease were very low (below 10%). Factors associated with vaccination uptake included individual characteristics, socioeconomic factors, and access to vaccination services. The findings highlight the need to implement integrated vaccination programs within educational institutions, along with strengthening health education and communication, as well as financial support policies, to improve vaccination coverage among medical students.